Chemical and genetic diversity of Baccharis dracunculifolia DC. (Asteraceae) from the Cerrado biome - Rigotti, Marcelo [UNESP]; Facanali, Roselaine; Haber, Lenita Lima; Vieira, Maria Aparecida Ribeiro [UNESP]; Isobe, Mônica Tiho Chisaki [UNESP]; Cavallari, Marcelo Mattos; Bajay, Miklos Maximiliano; Zucchi, Maria Imaculada; Pinheiro, José Baldin; Marques, Marcia Ortiz Mayo (Elsevier, 2023)
The essential oil of four populations of Baccharis dracunculifolia was analyzed for their chemical composition by CG/MS and the study of genetic diversity was conducted by analyzing the DNA polymorphism using microsatellite markers. The predominant compounds were E-nerolidol, cis-β-guaiene, germacrene D, E-caryophyllene, limonene, α-pinene, β-myrcene, δ-cadinene, β-pinene and spathulenol. The E-nerolidol substance was the most abundant among the compounds present in the essential oil in all populations. Genetic analysis showed that most of the diversity of B. dracunculifolia was within populations, and the diversity among populations is not expressive. All the populations evaluated in this study were in a process of extensive fragmentation, this might be the main cause of reduced genetic diversity of this specie in Cerrado biome. The comparison between PCA of genotypes and chemodiversity reinforces the unique profile for each population despite the environmental similarity observed and genetic analysis. The results obtained in this work, using microsatellite markers, made it possible to assess the genetic variability in natural populations of B. dracunculifolia.
Keywords: Alecrim-do-campo; Baccharis dracunculifolia; Cerrado; Essential oil; Genetic diversity